The Effect of Connected “Smart” Inhalers on Medication Adherence - Zabczyk, Caroline; Blakey, John D. (Frontiers in Medical Technology, 2021)
Asthma and chronic obstructive pulmonary disease (COPD) are highly prevalent worldwide, and major sources of morbidity. Key barriers to reduce the harm from these conditions are the widespread and related issues of low use of prescribed inhaled therapy, use of medicines differently from that prescribed, suboptimal inhaler technique, and lack of adherence are the action plans. Connected smart inhalers show great potential to improve these issues, and thus outcomes from airways disease. In this mini-review, we considered the published evidence that the use of smart inhalers leads to more doses of preventative treatment being taken on time and with appropriate techniques. We found multiple trials across a variety of settings and age groups where smart inhalers were used with audio-visual reminders and healthcare professional feedback, which substantially improved the number of doses of preventative treatment taken. Trial evidence also supports the use of feedback from smart inhalers in improving true concordance (doses taken correctly and on time), though only for a single type of smart device. The relative lack of study is in contrast with the potential impact of smart inhalers. Major research questions remain unresolved, as who might fund future large-scale studies, how guideline committees may consider them, and how to implement effective solutions.